ANALISIS BUTIR SOAL UJIAN SEMESTER GANJIL KELAS V SD NEGERI 163 PEKANBARU TAHUN PELAJARAN 2016/2017 - Oeleo, Sri; Marhadi, Hendri; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to find out the quality of grain of odd semester exam of grade V SD Negeri 163 Pekanbaru in the academic year 2016/2017 in terms of conformity with indicators, difficulty level, distinguishing factor, validity of item and test reliability. This research type is descriptive Quantitative by using statistical calculation. The study population included all students of grade V of SD Negeri 163 Pekanbaru as many as 177 people. The subjects of this study are the students of grade V of SD Negeri 163 Pekanbaru and grain of the odd semester exam of academic year 2016/2017 in class V SD Negeri 163 Pekanbaru. The items used are the items of Indonesian, Mathematics, Science, Social Studies and Civics which are subjects held by every homeroom teacher in the school. The result of the analysis of the odd semester test item in grade V of SD Negeri 163 Pekanbaru when viewed in terms of construction, materials, and language is categorized very well. The results of the research Based on the validity of the items indicate that the valid item grains totaling 112 items and the items are invalid amounted to 63 grains. Based on Reliability including the problem that has a high reliability of 0.84. Based on the Power of Differentiating the problem with good category consists of 28 items with very good distinguishing power, 33 items good question, 39 items enough, 58 items about ugly, and 16 items very ugly matter. Based on the level of difficulty as a whole indicates that the item is very difficult 3 grains, hard 7 grains, medium 75, easy 51 grains, and very easy 39 grains. Of the overall items raised in the test that obtained good soso and can be used as much as 75 items with 42.8% of the items must be fixed 58 by 33.2%, and 42 items with 24% can not be used. Keywords: Analysis of Test Items, Semester Exam Tests